Operational Risk Implications; A Case Study of Locally Incorporated European Bank - Allabasc, Nizam Shah; Ramasamy, Ravindran (School of Social Sciences, USM, 2017)
The purpose of this study is to examine the implication of the operational risk in the locally incorporated European Bank in Malaysia. The operational risk constitutes a small part of a bank’s risk profile which includes unpredicted measures that might possibly source the failure of the whole bank. Therefore, the bank has implemented permanent control plan methods which arise from the annual risk assessment plan. Moreover, the Permanent Control Plan for each department of the bank resulting in the process and procedure review on the risk assessment task to reduce or eliminate unwanted issues and problems arise from the process and system in the organisations. Each risk assessment activity with the permanent control plan was approved by the bank’s top level management before executed by phases in the year. There are 4 phases’ in the permanent control plan; monthly, quarterly, half yearly and yearly. In this study the researchers has looked into the half yearly control plan. The half yearly permanent control plan exercise executed by the Operational Risk Officer found non-compliance issues on a few department's work processes. As a result, a few key operational risk management implications faced by the bank with this incompliance activity. Besides that, the issues identified in this study was firm enough to address a major operational risk implication to the bank. Furthermore, there was no any action taken by the Permanent Control Manager to prevent this incompliance activity in future. As a conclusion, the results obtained from this study is necessary due to the operational loss and the reputational risks faced by the financial organization.